Geologi Dan Studi Faktor Keamanan Lereng Embung Klonggean Desa Siwalan Kecamatan Sawahan Kabupaten Nganjuk Provinsi Jawa Timur - Adam, Ignasius Mahendradewa (Jurnal Ilmiah MTG, 2023)
This study aims to determine the geological conditions of the research area and to analyze and determine the stability of the slopes of the Klonggean dam based on the calculation of the safety factor of the slope by analyzing the stability of the slope in terms of the intensity of the slide (Bowles1984). The method used is the analysis of the slope factor of safety using Simplified Bishop Method use RoscienceSlide 6.0 software and graphical methods Hook and Bray (1981) which performed calculations manually. The results of the analysis get a factor of safety (FK) that is not much different and both are in the safe/stable category (slides rarely occur)) (Bowles 1984): 1. The results of the analysis of slope stability with Bishop Simplified Method use RocsienceSlide 6.0 Software obtained FK value of 2.944 (FK> 1.25). 2. The results of the analysis using the graphical method Hook and Bray obtained a safety factor value of 2.794 (FK> 1.25).